2003
DOI: 10.17221/4155-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cropping system and genotype on variability in important phytonutrients kontent of the barley grain for direct food use

Abstract: In a four-year period (1997)(1998)(1999)(2000), selected phytonutrients, of which the beta-glucan content is most important for human health, were studied in caryopses of different types of barley varieties and lines (standard, waxy, hulless) from two cropping systems. It was significantly highest in the waxy variety Washonubet (4.93%). The whole group of waxy types of barley showed a significantly higher mean content of beta-glucans (4.75%) than the varieties with standard starch composition (4.12%), the star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…High temperature during growing season and drought before grain harvest (SAVIN and MOLINA-CANO, 2001) could increase the content of β-D-glucan in oat grains. The same effect has been observed in barley EHRENBERGEROVÁ et al (2003). The authors concluded that the contents of β-D-glucan and arabinoxylans were significantly affected by genotype, environmental conditions during the vegetation period and by their interactions.…”
Section: β-Glucans Under Heat Stresssupporting
confidence: 61%
“…High temperature during growing season and drought before grain harvest (SAVIN and MOLINA-CANO, 2001) could increase the content of β-D-glucan in oat grains. The same effect has been observed in barley EHRENBERGEROVÁ et al (2003). The authors concluded that the contents of β-D-glucan and arabinoxylans were significantly affected by genotype, environmental conditions during the vegetation period and by their interactions.…”
Section: β-Glucans Under Heat Stresssupporting
confidence: 61%
“…Increased levels of β-glucan have been reported in hull-les waxy barley (Ehrenbergerová et al 2003(Ehrenbergerová et al , 2008Procházková et al 2004), its content being affected by the enrironmental conditions and their interactions with varieties (Ehrenbergerová et al 2008). Hull-les barley has been successfully used (Bhatty 1986) and the effects on the baking properties of flour used in bakery products and bread have been determined (Newman et al 1990;Andersson et al 2004).…”
Section: Dietary Fibrementioning
confidence: 99%
“…IV). EHRENBERGEROVÁ et al (2003) found in their set of waxy and non-waxy genotypes signifi cantly higher starch content in the standard varieties than in the waxy types. Based on the correlation analysis (Tab.…”
Section: Ii: the Eff Ect Of The Individual Factors On Variability Of mentioning
confidence: 88%